Strength Analysis of Deck A KM. Dharma Kencana V Due to The Addition of Construction With The Finite Element Method - Rizki, Muhammad Khoirur; Arianto, Pratama Yuli; Sumarji, Sumarji; Rudianto, Rudianto (Indonesian Journal of Maritime Technology, 2025)
The Dharma Kencana V passenger ship is a type of crossing ship owned by a Japanese shipping company which was later acquired by an Indonesia shipping company whose planned shipping route crosses from Surabaya to Makassar. With the transfer of the ship’s shipping route, repairs and the addition of new construction in the deck A area were carried out so that the addition of the new construction increased the load the ship received. This study aims to determine the allowable stress allowed by the Indonesian Classification Bureau (BKI) Rules for Hull 2022 [1] from the stress results due to new construction on the deck. The analysis was carried out using the finite element method with numerical modeling using Ansys Static Structure student version software with a division of elements (meshing) size 200 mm on deck A frame 13 to 85. Based on the results of the element division of deck KM. Dharma Kencana V into 44767 elements at nodes 45384 and the maximum stress at 77.41 MPa. The allowable stress limit based on the BKI standard does not exceed 230 MPa, [1] so a safety factor of 2.97 is obtained so it can be concluded that the strength of the construction of deck A KM. Dharma Kencana V is still a safe category.